2011
DOI: 10.1063/1.3567635
|View full text |Cite
|
Sign up to set email alerts
|

Stable high conductive amorphous InGaZnO driven by hydrogenation using hot isostatic pressing

Abstract: We carried out hydrogen injection in amorphous InGaZnO (a-IGZO) by hot isostatic pressing (HIP) treatment under different pressures ranging from 10 to 1000 bar and investigated the stable site of hydrogen in a-IGZO. The HIP process efficiently injected hydrogen in the whole sample without the formation of indium clusters. Despite oxygen annealing, hydrogenated a-IGZO maintained a high electrical conductivity (n∼1019 cm−3 and μ∼16 cm2/V s) without any noticeable physical degradation. In this paper, we discuss t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Highly oriented phases of XRD peaks were measured, even though the ZnO was deposited by sputtering at room temperature. The full-width at half-maximum (FWHM) of XRD spectra are comparable with the data of ZnO published in literature 34 , 35 , while the IGZO has an amorphous structure 36 .
Figure 4 ( a ) SIMS depth profile of ZnO on HfO 2 /TiO 2 /SiO 2 stacked gate dielectrics, ( b ) Cross-sectional TEM and ( c ) XRD spectra of ZnO/high-κ/TaN structure on flexible PEN substrate.
…”
Section: Resultssupporting
confidence: 84%
“…Highly oriented phases of XRD peaks were measured, even though the ZnO was deposited by sputtering at room temperature. The full-width at half-maximum (FWHM) of XRD spectra are comparable with the data of ZnO published in literature 34 , 35 , while the IGZO has an amorphous structure 36 .
Figure 4 ( a ) SIMS depth profile of ZnO on HfO 2 /TiO 2 /SiO 2 stacked gate dielectrics, ( b ) Cross-sectional TEM and ( c ) XRD spectra of ZnO/high-κ/TaN structure on flexible PEN substrate.
…”
Section: Resultssupporting
confidence: 84%
“…However, It was reported that hydrogen plays not only as a shallow donor 21 but also as a scattering center in the conduction path. 22,23 Therefore, the carrier scattering induced by hydrogen is one possible reason for the decrease in carrier mobility mentioned above. The free hydrogen and hydrogen contained compounds in a sputtering chamber and in a sputtering target can play as the sources for hydrogen in IGZO film.…”
Section: Resultsmentioning
confidence: 99%
“…For hydrogen treatment, hot isostatic pressing (HIP) was used. The HIP method injects hydrogen into the samples more effectively under high pressure and temperature without damage, whereas hydrogen plasma treatment can cause surface damage due to the high reaction energy …”
Section: Methodsmentioning
confidence: 99%